Patterns of psychiatric healthcare use during pandemic times among boys and girls with pre-existing diagnoses: a Norwegian nationwide primary and specialist healthcare registry study - Ingunn Olea Lund; Pia Jensen; Christian Madsen; Lars Johan Hauge; Alexandra Havdahl; Anne Reneflot; Ragnhild Brandlistuen; Helga Ask (BMC Psychiatry)
Abstract Background The COVID-19 pandemic introduced complexities that were likely more demanding for some groups, such as children and adolescents, and especially those with pre-existing mental health diagnoses. This study examines long-term patterns of psychiatric healthcare use among this vulnerable group, providing insights into shifts in psychiatric healthcare use during a global health crisis. Methods We use data from the primary and specialist healthcare registries available from the Norwegian emergency preparedness register for COVID-19 (Beredt C19) to estimate patterns of psychiatric healthcare use. The data spans 2017 to 2022, covering children and adolescents aged 6–19. We identified young people with recent diagnoses of mental health conditions and compared weekly consultation volumes before and during the pandemic for mental health conditions overall and the following diagnostic or symptom categories separately: anxiety/depression and Attention-Deficit Hyperactivity Disorders (ADHD). Analyses were stratified by gender. Results There was a consistent trend of lower-than-predicted weekly healthcare consultations among young people with pre-existing mental health diagnoses in both primary and specialist healthcare during the pandemic. The reduction was more pronounced in later follow-up periods. The study highlights gender disparities, with boys experiencing more notable declines in healthcare consultations, especially in specialist care. Additionally, the time trends varied across different diagnostic groups. While consultations for anxiety/depression were consistently below the predicted levels, declines in ADHD occurred later in the pandemic. The data suggests an overall decline in healthcare use rather than a shift between sectors. Conclusion The findings offer insights into healthcare use during pandemic times among children and adolescents with pre-existing mental health diagnoses. The study underscores the importance of continuous monitoring and support for this group, ensuring accessible and responsive healthcare during public health emergencies.